Direct current transport mechanisms in n-InSe/p-CdTe heterostructure - Gorley, P.M.; Prokopenko, I.V.; Grushka, Z.M.; Makhniy, V.P.; Grushka, O.G.; Chervinsky, O.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The authors created n-InSe/p-CdTe heterojunction by deposition over optical
contact, investigated temperature evolution of its current-voltage dependences under the
forward bias, and determined the prevailing current transport mechanisms in the
structure. It was shown that misfit dislocations at the boundary between the
semiconductors form a stable periodic structure acting as slow recombination centers for
the carriers. The properties of the material suggest promising application perspectives for
n-InSe/p-CdTe heterojunction, especially for the devices working at high temperatures
and elevated radiation.